German translation and validation of the Pelvic Organ Prolapse/Incontinence Sexual Questionnaire–IUGA revised (PISQ-IR). Issue 8 (August 2016) - Trutnovsky, Gerda; Nagele, Eva; Ulrich, Daniela; Aigmüller, Thomas; Dörfler, Daniela; Geiss, Ingrid; Reinstadler, Evi; Angleitner-Flotzinger, Johannes; Ries, Jean-Jacques; Bjelic-Radisic, Vesna
Abstract Introduction and hypothesis Condition-specific sexual questionnaires are essential for clinical trials and important patient-reported outcome measures. The aim of the study was to translate the Pelvic Organ Prolapse/Incontinence Sexual Questionnaire–International Urogynecology Association Revised (PISQ-IR) into German and to clinically validate it in a German-speaking population. Methods The translated PISQ-IR was linguistically validated in two rounds of cognitive interviews. The final instrument was psychometrically validated in women presenting to urogynecological clinics with pelvic floor dysfunction. For analysis of criterion validity, three related self-reported measures were administered: the Female Sexual Function Index (FSFI), the Kings Health Questionnaire (KHQ), and the 36-Item Short Form Health Survey (SF-36). For external validity, PISQ-IR subscales were compared to the clinical-measures Pelvic Organ Prolapse Quantification system (POP-Q) stage, pelvic floor muscle tone, and Oxford Grading Scale. Descriptive statistics, floor and ceiling effects, internal consistency using Cronbach's alpha coefficient, and Pearson correlations were calculated for all PISQ-IR subscales. Results The PISQ-IR was completed by 197 women, out of whom 66 (33.5 %) considered themselves not sexually active (NSA) and 131 (66.5 %) as sexually active (SA). Participants' mean age was 57 ± 12 years; 50 % were diagnosed with symptomatic POP, 74 % with urinary incontinence (UI) and 4 % with anal incontinence (AI). The PISQ-IR subscales were analyzed separately for SA and NSA women with Cronbach's alpha coefficients ranging from 0.64 to 0.94. Moderate to high correlations were observed between PISQ-IR subscales and related quality of life (QoL) scales and corresponding FSFI scales. Conclusion Initial testing of the German PISQ-IR suggests it is an internally consistent and valid tool for use in clinical practice and research.